Promoting peace and climate resilience in the post-conflict Mindanao region of the Philippines - Pacillo, Grazia; Savelli, Adam; Medina Santa Cruz, Leonardo (2025)
Researchers from the Alliance of Bioversity International and CIAT launched a first-ever community of practice on climate security and environmental peacebuilding and collaborated to identify entry points for environmental peacebuilding. The research team partnered with Mindanao State University - Iligan Institute of Technology (MSU-IIT) and contributed to CGIAR’s Climate Resilience Initiative (ClimBeR). The partnership supported MSU-IIT in securing the institution a seat on an influential committee for reintegrating conflict-affected communities into society. Now MSU-IIT can inform proposed climate-resilience interventions and ensure they also foster peacebuilding.